2016
DOI: 10.1002/bjs.10039
|View full text |Cite
|
Sign up to set email alerts
|

Changes in insulin sensitivity and secretion after sleeve gastrectomy

Abstract: Sleeve gastrectomy improved insulin sensitivity and reduced insulin secretion within 6 months after surgery. Although there was a correlation between insulin sensitivity and bodyweight, the major driver of the improvement in insulin sensitivity was GLP-1 secretion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 40 publications
1
16
1
Order By: Relevance
“…Consistent with our findings, Casella et al demonstrated that SG improved insulin sensitivity (euglycemic hyperinsulinemic clamp technique) and reduced insulin secretion (OGTT) within 12 months after surgery. The significant changes in insulin sensitivity and insulin secretion indices found in our study were not related to weight loss in the first month follow-up, which might be explained by the early postoperative hormonal changes induced by SG (10,27).…”
Section: Discussioncontrasting
confidence: 57%
“…Consistent with our findings, Casella et al demonstrated that SG improved insulin sensitivity (euglycemic hyperinsulinemic clamp technique) and reduced insulin secretion (OGTT) within 12 months after surgery. The significant changes in insulin sensitivity and insulin secretion indices found in our study were not related to weight loss in the first month follow-up, which might be explained by the early postoperative hormonal changes induced by SG (10,27).…”
Section: Discussioncontrasting
confidence: 57%
“…Bariatric surgery can be extremely effective for long-term body weight loss and amelioration of the comorbidities of obesity (5, 7, 12, 14). About 80% of the recipients of surgical weight loss are women of whom approximately half are of child bearing age.…”
Section: Introductionmentioning
confidence: 99%
“…Peterli et al [ 30 ] have found that postprandial plasma insulin is higher in RYGB patients than in SG patients one week postoperatively, but both surgery groups exhibit similar insulin levels at three months. Although there was a correlation between insulin sensitivity and body weight, the major driver of the improvement in insulin sensitivity after SG was GLP-1 secretion [ 31 ]. Changes in GLP-1 are often considered a mechanism for the weight-independent effects of bariatric surgery on glucose homeostasis, which may explain why purely restrictive procedures or nonsurgical weight loss have little effect on glucose control [ 32 ].…”
Section: Discussionmentioning
confidence: 99%